Prions and humans (A brief review of human prion diseases) - Koren, Srečko (Agricultura Scientia, 2020)
Prion diseases, or transmissible spongiform encephalopathies are a group of neurodegenerative diseases that affect humans and animals. Prion diseases are manifest as infectious, genetic or sporadic disorders. They can be transmitted among different hosts by the infectious proteinaceous particles, called prions. Prions (PrP) are derived from a normal cellular isofrom PrPc after posttranslational conformational modification to PrPSc. New variant Creutzfeldt-Jakob disease (vCJD) is a novel human prion disorder with characteristic clinical and neuropathological features, which results from exposure to the prions causing bovine spongiform encephalopathy in cattle. Further studies are required to clarify risk factors and the possibility that the vCJD might spread from person to person by blood transfusion or by surgical procedures.Presented at the International Conference: “Tell me what you eat, and I will tell you who you are – when BSE in Slovenia?”, 4-5 October 2000, Maribor, Slovenia
Keywords: prions; prion diseases; prinew variant Creutzfeldt-Jakob disease